DESCRIPTIVE STUDY OF YOUTH RED CROSS COMPETENCE AT MADRASAH ALIYAH NEGERI 1 PASURUAN - Wati, Sinta Hijriyah; Dari, Tanty Wulan (Global Ten Public Health and Nursing Journal, 2023)
One type of extracurricular activity in schools is the Youth Red Cross (PMR). The Youth Red Cross extracurricular activity is an activity that instills an attitude of social concern, an attitude of responsibility, and a high sense of cooperation. In school-age children, these activities are more directed at medical treatment, placing stretchers, and other health activities that can create a high sense of cooperation, solidarity, responsibility, sincerity, discipline, and high concern so that they are expected to form character and social skills. each individual from the Youth Red Cross extracurricular activities. This research was conducted to determine and identify the competence of the Youth Red Cross at Madrasah Aliyah Negeri 1 Pasuruan. This study used a descriptive research design. The research subjects took 26 samples from 26 youth red cross members at Madrasah Aliyah Negeri 1 Pasuruan using total sampling technique. This research was conducted by giving a questionnaire. The results of this study indicate that of the 26 members of the Youth Red Cross at Madrasah Aliyah Negeri 1 Pasuruan, all of them have good abilities, namely 26 students (100%). Based on the results of the study, all of them had good abilities, namely 26 students (100%). This was because all members of the Youth Red Cross attended routine training well once every 1 week, so that the material studied was assimilated and linked to the knowledge students already had. in the form of a cognitive structure Keywords: Competence, Youth Red Cross